Reproduction criteria and meat quality of South African Black (Struthio Camelus var. Domesticus), Zimbabwean Blue (Struthio Camelus Australis) and South African Black X Zimbabwean Blue ostriches - Brand, Monica Merenza (Stellenbosch : University of Stellenbosch, 2008)
Thesis (Msc Food Sc (Food Science))--University of Stellenbosch, 2006.